2015
DOI: 10.1016/j.jaci.2014.09.031
|View full text |Cite
|
Sign up to set email alerts
|

The draft genome, transcriptome, and microbiome of Dermatophagoides farinae reveal a broad spectrum of dust mite allergens

Abstract: An HDM genome draft produced from genomic, transcriptomic, and proteomic experiments revealed allergen genes and a diverse endosymbiotic microbiome, providing a tool for further identification and characterization of HDM allergens and development of diagnostics and immunotherapeutic vaccines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
170
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(183 citation statements)
references
References 44 publications
(47 reference statements)
6
170
1
2
Order By: Relevance
“…Randall et al [1] help explain this in an analysis of their assembly of the genomic sequence of Derma tophagoides pteronyssinus. The assembly, also reported by Waldron et al [2], in fact follows those for D. farinae [3] and the closely related Euroglyphus maynei [4], but for the first time attention is directed to the issues that are important for allergy research, going beyond being a tool for the verification of newly discovered allergens. The completeness of the coverage of a genome assembly is a critical starting point for all genomic projects so considerable attention is given to the sequencing metrics, which showed high indicators of success.…”
supporting
confidence: 57%
See 1 more Smart Citation
“…Randall et al [1] help explain this in an analysis of their assembly of the genomic sequence of Derma tophagoides pteronyssinus. The assembly, also reported by Waldron et al [2], in fact follows those for D. farinae [3] and the closely related Euroglyphus maynei [4], but for the first time attention is directed to the issues that are important for allergy research, going beyond being a tool for the verification of newly discovered allergens. The completeness of the coverage of a genome assembly is a critical starting point for all genomic projects so considerable attention is given to the sequencing metrics, which showed high indicators of success.…”
supporting
confidence: 57%
“…It was similarly left unassigned by Chan et al [3] for D. farinae. The homologues include those of the newly described Der f 24-34 allergens that were mostly identified in proteomic screens in China and have yet to be assessed for their IgE binding by gravimetric estimates or by titrations compared to the serodominant group 1 and 2 allergens.…”
mentioning
confidence: 99%
“…As we also demonstrated that rDer p 23 could not bind to chitin structures present on the surface of mite fecal pellets, we speculate that the localization of Der p 23 into the peritrophic matrix of the mite could result from interactions with molecular partners other than chitin, or from the existence of oligomeric forms of the allergen exposing the appropriate 4-cysteine-based chitin-binding domains to interact with chitin. It must also be pointed out that the Der f 23 amino acid sequence was shown to contain a putative chitin binding domain with 5 cysteine residues; 4/5 cysteine residues are conserved in Der p 23 [22]. However, the chitin-binding properties of Der f 23 have yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Once the process of sensitization has begun with Der p 1, lower concentrations of Der p 2 may find a sufficiently proallergenic milieu to also achieve sensitization. Of course, this is mainly speculation, and the different biochemical functions of both allergens may play a role jointly or individually [23][24][25][26][27][28] . Der p 1 belongs to the papainlike cysteine protease family with cysteine protease activity [23,24] .…”
Section: Discussionmentioning
confidence: 99%